Buddhist-Muslim relationship through local wisdom as a form of multicultural education - Suranto, Suranto (Indonesian journal of religion, spirituality and humanity, 2024)
While not particularly prominent in broader interfaith dialogues, the Buddhist-Muslim relationship is a tangible reality in the Kaloran community, Temanggung. This qualitative study aims to explore the Buddhist-Muslim relationship through the local wisdom that has developed in the community. Data was collected through observation, interviews, documentation, and focus group discussions (FGD). The collected data was then subjected to descriptive synthesis analysis. The relationship between Buddhist and Muslim communities can be fostered through local wisdom as part of implementing living religious values. This local wisdom is divided into three thematic groups: 1) local wisdom without text, in the form of expressions or wisdom that serve as principles and guidelines for the life of a multicultural society; 2) local wisdom in the form of ritual symbols that serve as a medium for dialogue in a multicultural society; and 3) local wisdom in the form of performing arts that serve as a medium for dialogue in a multicultural society. Based on the sociology of religion approach and lived religion, local wisdom is part of the flexible media used by the Buddhist community to maintain relations with Muslims. This local wisdom serves as a medium for relations in order to maintain the harmonious life of a multicultural society.